Chemoimmunotherapy Drugs with Antiviral Activity to Treat Patients with Lung Cancer and COVID-19; a Narrative Review - Olfati, Ali; Soufivand , Parviz; Saadatfar , Abdollah (Archives of Men's Health, 2023)
Every year lung cancer is a cause of high morbidity and mortality in the human population. However, since 31 December 2019, the coronavirus disease 2019 [COVID-19] had importantly affected various degrees of pulmonary regions. Therefore, patients with lung cancer must be the priority group for COVID-19 prevention, treatment, and vaccination during the COVID-19 pandemic. Until now, clinicians and patients know that most individuals with respiratory distress and/or those with a weakened immune system are more susceptible to COVID-19, however, the associations with lung cancer remain unclear. Here, we present the combination of common chemotherapeutic drugs with a historical antiviral activity that may be too immunosuppressive to eliminate COVID-19-infected cells in patients with lung cancer. This review will help understand the preferred chemoimmunotherapy drugs for severe forms of COVID-19 [SARS-CoV-2] in these patients.